2014
DOI: 10.1021/om5004336
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated 2-Phenylimidazole Palladium Carbene Complexes in the Catalytic Suzuki–Miyaura Cross-Coupling Reaction

Abstract: We present the syntheses of 12 cyclometalated palladium C ∧ N 2-phenylimidazole carbene complexes with different N-1 groups as well as different substituents at the C-2 phenyl group of the cyclometalating imidazole. We investigated the influence of these substituents by comparing the catalytic performance of the complexes in the Suzuki−Miyaura cross-coupling reaction of aryl chlorides. We can show a strong dependence between the steric demand of the N-1 substituent of the cyclometalating imidazole and the cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…However, it is unlikely that a quantitative in-situ complex formation occurs in a short reaction time, which leads to a waste of palladium source and ligand. [36][37][38] A series of benzimidazolium-pyrazole palladium complexes have been successfully developed by Andy Hor and his collaborators, [39] which showed high catalytic activity for cross-coupling of aryl halides with arylboronic acids under homogeneous conditions. [27][28][29] Recently, several air-stable phosphine-free palladium complexes have been reported for use in the Suzuki-Miyaura cross-coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unlikely that a quantitative in-situ complex formation occurs in a short reaction time, which leads to a waste of palladium source and ligand. [36][37][38] A series of benzimidazolium-pyrazole palladium complexes have been successfully developed by Andy Hor and his collaborators, [39] which showed high catalytic activity for cross-coupling of aryl halides with arylboronic acids under homogeneous conditions. [27][28][29] Recently, several air-stable phosphine-free palladium complexes have been reported for use in the Suzuki-Miyaura cross-coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Organ and co‐workers reported that (NHC)PdCl 2 (pyridine) were more active than their 3‐chloropyridine analogues, due to either a higher dissociation rate of pyridine or a higher tendency to re‐coordinate to [(NHC)Pd(0)] species . Based on this, other types of N‐donors have received attention and been introduced into the coordination with NHC–Pd complexes, including triethylamine, diethylamine, 1‐methylimidazole, 2‐phenyl‐4,5‐dihydrooxazole, morpholine, 2‐phenylimidazole, acetonitrile, benzoxazole (benzothiazole), http://pubs.rsc.org/en/content/articlelanding/2016/ob/c6ob00013d, 1‐methylpyrazole (1‐methylindazole), etc. All of them have shown promising catalytic activity in organic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…The first report on an application of a cyclopalladated trio-tolyl-phosphine complex for cross-coupling reactions by Herrmann and co-workers 32 raised high expectations for the palladacycles. Since then several groups have shown interest in synthesizing CN, [33][34][35][36][37][38][39][40][41][42][43][44][45][46] CS, 47,48 and CP 32,[49][50][51][52][53] palladacycle catalysts or precatalysts and pincer [54][55][56][57] palladium complexes. The CN palladacycles [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] gained attention since the pioneering work of Milstein and co-workers, 33 who introduced a wide variety of imine-based palladacycles for the cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Since then several groups have shown interest in synthesizing CN, [33][34][35][36][37][38][39][40][41][42][43][44][45][46] CS, 47,48 and CP 32,[49][50][51][52][53] palladacycle catalysts or precatalysts and pincer [54][55][56][57] palladium complexes. The CN palladacycles [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] gained attention since the pioneering work of Milstein and co-workers, 33 who introduced a wide variety of imine-based palladacycles for the cross-coupling reactions. The importance of CN palladacycles was expanded significantly by Buchwald, 40 Gladysz, 36 Najera,…”
Section: Introductionmentioning
confidence: 99%